Plasmon-enhanced-attosecond-extreme ultraviolet source - Lupetti, Mattia; Kling, Matthias F.; Scrinzi, Armin (My University, 2013)
A compact high repetition rate attosecond light source based on a standard laser oscillator combined with plasmonic enhancement is analyzed. At repetition rates of tens of MHz, we predict focusable pulses with durations of ≲300 as and a spherical wave front at collimation angles ≲5° . Plasmonic mode and guiding of the attosecond radiation determine the beam parameters. The beam is robust with respect to variations of driver pulse focus and duration.
Keywords: Light; Ultraviolet; Electronic dynamics; Attosecond pulse